2011
DOI: 10.1901/jeab.2011.96-139
|View full text |Cite
|
Sign up to set email alerts
|

Matching‐and Nonmatching‐to‐sample Concept Learning in Rats Using Olfactory Stimuli

Abstract: Previous research has shown that rats can learn matching-to-sample relations with olfactory stimuli; however, the specific characteristics of this relational control are unclear. In Experiment 1, 6 rats were trained to either match or nonmatch to sample in a modified operant chamber using common household spices as olfactory stimuli. After matching or nonmatching training with 10 exemplars, the contingencies were reversed with five new stimuli such that subjects trained on matching were shifted to nonmatching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
3
22
0
2
Order By: Relevance
“…Indeed, the results of Experiment 2 are noteworthy on their own account. Although previous research from our laboratory has demonstrated generalized matching‐ and nonmatching‐to‐sample with olfactory stimuli, these studies used manual training arrangements in which rats responded by digging in scented sand (April et al, ; Pena et al, ) or responding to scented lids (April et al, ). Lu et al () showed rapid acquisition of identity matching‐to‐sample using an automated go/no‐go arrangement much like the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the results of Experiment 2 are noteworthy on their own account. Although previous research from our laboratory has demonstrated generalized matching‐ and nonmatching‐to‐sample with olfactory stimuli, these studies used manual training arrangements in which rats responded by digging in scented sand (April et al, ; Pena et al, ) or responding to scented lids (April et al, ). Lu et al () showed rapid acquisition of identity matching‐to‐sample using an automated go/no‐go arrangement much like the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Iversen (; ) trained rats on visual identity matching‐to‐sample procedures and found that acquisition was slow and further complicated by stimulus location control. In contrast, our laboratory has found fairly rapid acquisition of matching‐ and nonmatching‐to‐sample relations when rats were trained to dig in scented sand or respond to scented objects on simultaneous conditional discriminations, and that control by generalized same–different relations emerged following such training (April, Bruce & Galizio, , ; Pena, Pitts & Galizio, ). Rapid acquisition of matching‐to‐sample has also been demonstrated with odor stimuli using successive discrimination procedures (go/no‐go) in rats (Lu, Slotnick & Silberberg, ).…”
mentioning
confidence: 93%
“…De modo geral, os estudos sobre discriminação condicional com ratos empregam uma modalidade única de estímulos (e.g., estímulos olfatórios -Peña, Pitts & Galizio, 2006; estímulos visuaisNakagawa, 2005) e tarefas de IMTS (April, Bruce & Galizio, 2011;Iversen, 1993Iversen, , 1997. O ensino de relações condicionais arbitrárias via tarefas de MTS para ratos é pouco comum e, para tentar minimizar as dificuldades encontradas em outros estudos, optou-se por adotar um procedimento de correção de tentativas.…”
Section: Discussionunclassified
“…Estudos empregando estímulos olfatórios e IMTS demonstraram a ocorrência de emparelhamento generalizado por identidade em ratos (April et al, 2011;Peña et al, 2006). Nesses estudos, respostas de observação são exigidas do animal, o que pode ter aumentado o grau de contato deles com aspectos relevantes do estímulo e favorecido o desempenho relacional exigido na tarefa.…”
Section: Discussionunclassified
“…We assessed the potential for training a generalist dog to reliably detect many plant species using a match‐to‐sample (MTS) procedure (April et al ., ). A generalist plant detector provides operational efficiencies relative to a specialist dog, as most agencies are likely to need to search for different plant species at different times.…”
Section: Introductionmentioning
confidence: 97%